Penerapan Metode Problem Based Learning dalam Pembelajaran PKn untuk Membangun Budaya Demokrasi Peserta Didik - Ramdan Darmawan; Sri Devi Rahmawati; Rifqi Fadli Robby Al-Fathy; Endang Dimyati; Tetep; Cecep Kuswara (Cipta Media Harmoni, 2025)
The problem of students' democratic culture is often caused by the learning process that is still dominated by the teacher. This study aims to assess the extent to which the Problem Based Learning (PBL) method in Civics learning is effective in building students' democratic culture. The approach used in this research is classroom action research (PTK) using the Kemmis & Taggart model consisting of two cycles with two meetings, where each cycle goes through four stages, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The research sample was determined through purposive sampling technique, with class IX-A as the research object. Data were collected through interviews, observations and documentation. Data analysis was carried out using descriptive percentage techniques in accordance with Civics learning outcomes. The results of hypothesis testing show that the application of PBL method in Civics learning has a positive influence on the development of students' democratic culture. This increase can be seen from the increase in each cycle, in terms of student participation experiencing an average increase of around 20%, an increase in student confidence in expressing opinions increased by 37.5%, and also mutual respect with an average increase of around 22.5%, meaning that this can be said to have met the specified target. Based on these results, it can be concluded that the Problem Based Learning (PBL) method in Civics learning has proven effective in building a culture of democracy in students.